Unilateral Beach Reclamation Land in Relation to the Decision of the DKI Jakarta High Court Number 129/PDT/2022/PT DKI - Silvia Indah Melani; Moh. Asep Suharna; Tuti Herawati (CV. Publikasi Indonesia, 2025)
Coastal reclamation is a land management strategy aimed at increasing the socio-economic and environmental benefits of coastal areas. However, it often leads to legal conflicts concerning land ownership, particularly when such reclamations are carried out without appropriate permits. This research aims to analyze the legal status of land rights for parties who carry out coastal reclamation by reviewing the DKI Jakarta High Court Decision Number 129/PDT/2022/PT DKI. The method used is a normative juridical approach by analyzing relevant laws and court decisions. The results show that reclaimed land is state land whose management is subject to strict regulations. In the case studied, PT Pelayaran Menaratama Samudra Indah was proven to have carried out reclamation without a valid permit, so it was declared unlawful by the DKI Jakarta High Court. In conclusion, any form of reclamation must comply with applicable regulations so as not to cause legal implications for the perpetrators and the surrounding community.